The Effect of The Organizational Citizenship and Cynicism Behaviors on The Management of Hierarchical Conflicts - Yılmaz, Hakan; Şencan, Hüner (International Review of Management and Marketing, 2018)
The increase in organizational effectiveness and productivity is significantly related to employees' and managers' performance. In this base, it is important to determine the attitudes and behaviors of managers and their subordinates during the conflict management process. In this research, the relationships between organizational citizenship behavior (OCB), hierarchical conflict management (HCM) and organizational cynicism behavior (CB) were investigated within the scope of demographic variables. In this manner, the influence of OCB on HCM and on its sub-dimensions were measured. Moreover, the moderator effect of CB and demographic factors on the relation between OCB and HCM was tried to be identified. The population of this study is the financial sector employees in Turkey and the practice population is limited in terms of provinces and titles. Using the criterion, the pilot research was conducted with 201 respondents. The ultimate main research uses data from 384 questionnaires, selected through random sampling technique. Results achieved using IBM SPSS 17, FACTOR 10.3 and AMOS 21, indicated that the level of OCB of financial sector managers and their employees has a significant effect on HCM and its sub-dimensions. Furthermore, CB, Title and Capital Structure variables moderates the relationship between OCB and HCM. Keywords: Organizational Citizenship Behavior, Conflict Management, Organizational Cynicism Behavior. JEL Classifications: D23, D74, M10